(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Minimally invasive surgery (MIS) has revolutionized the field of oncogynecology by offering effective tumor control with reduced perioperative morbidity. This review evaluates the role of laparoscopic and robotic-assisted techniques in the treatment of gynecological malignancies, including endometrial, cervical, and ovarian cancers. We analyze current evidence regarding oncologic safety, survival outcomes, and the impact on patients’ quality of life. The integration of MIS into standard oncological care represents a paradigm shift that emphasizes patient-centered, individualized treatment.